Roman Catholic Cathedral, Trinidad, B.W.I. - (:unkn) unknown (Photogelatine Engraving Co. Limited, 2010)
Image depicts a view of the Roman Catholic Cathedral, also known as the Cathedral of the Immaculate Conception. The cathedral is located in the capital city of Port of Spain, on the island of Trinidad, in the twin-island Republic of Trinidad and Tobago. Postcard number 404.
Colour: Shades of Red, Green, Yellow, Blue and Gray; Style: Landscape; Other: Unbordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Catholic Church--Trinidad and Tobago; Church buildings--Trinidad and Tobago; Christianity--Trinidad and Tobago; Catholics--Trinidad and Tobago; Catholic church buildings--Trinidad and Tobago; Church architecture--Trinidad and Tobago; Architecture--Details; Cathedrals--Trinidad and Tobago; Clocks and watches--Trinidad and Tobago; Towers--Trinidad and Tobago; Gates--Trinidad and Tobago; Fences--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; [1900]; Buildings--Trinidad and Tobago; Architecture--Trinidad and Tobago; Marine Square (Port of Spain); Independence Square (Port of Spain)